EL DISCURSO DEL PROFESOR DE INGLÉS COMO L2 : DIFERENCIAS DISCURSIVAS NATIVO-NO NATIVO - Torreblanca López, María del Mar (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract L2 teacher discourse is a type of modified discourse, like caretaker speech, mother talk or foreigner talk. Teachers simplify their speech, trying to offer comprehensible input to their students in order to aid in their L2 acquisition. In this paper, we will concentrate on the differences found in the discourse of native and non-native teachers of English in a 26-hour corpus of EFL and ESL classes. Brown & Levinson‘s Politeness Theory (1978, 1987) will be the theoretical framework used to account for this use of language. The results indicate that the institutional setting in which the teachers are working is a major factor influencing their speech and it can even be more relevant than their mother tongue.